Study of excited charm-strange baryons with evidence for new baryons Xi(c)(3055)(+) and Xi(c)(3123)(+) - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2008)
We present a study of excited charm-strange baryon states produced in e+e- annihilations at or near a center-of-mass energy of 10.58 GeV, in a data sample with an integrated luminosity of 384fb-1 recorded with the BABAR detector at the PEP-II e+e- storage rings at the Stanford Linear Accelerator Center. We study strong decays of charm-strange baryons to Λc+KS0, Λc+K-, Λc+K-π+, Λc+KS0π-, Λc+KS0π-π+, and Λc+K-π+π-. This study confirms the existence of the states Ξc(2980)+, Ξc(3077)+, and Ξc(3077)0, with a more accurate determination of the Ξc(2980)+ mass and width. We also present evidence for two new states, Ξc(3055)+ and Ξc(3123)+, decaying through the intermediate- resonant modes Σc(2455)++K- and Σc(2520)++K-, respectively. For each of these baryons, we measure the yield in each final state, determine the statistical significance, and calculate the product of the production cross section and branching fractions. We also measure the masses and widths of these excited charm-strange baryons. © 2008 The American Physical Society.